Religious coping and hope in chronic kidney disease: a randomized controlled trial - Suzana Mara Cordeiro Eloia; Maria Aline Moreira Ximenes; Sara Cordeiro Eloia; Nelson Miguel Galindo Neto; Lívia Moreira Barros; Joselany Áfio Caetano (SciELO, 2021)
ABSTRACT Objective: To evaluate the effect of prayer on religious/spiritual coping and on the hope of patients with chronic kidney disease undergoing hemodialysis. Method: Randomized, controlled and blinded clinical trial, carried out in a dialysis unit, with a total of 62 patients undergoing hemodialysis - 31 participants in intervention group and 31 in the control group. Intercession prayer was applied three times, in alternate weeks, during hemodialysis sessions. Differences between groups in the outcome of the effect of prayer on religious/spiritual coping and hope were analyzed. Results: Participants used positive coping at high mean scores in both groups (control - 3.62 and intervention - 3.26) and negative coping had little use (control - 1.66 and intervention - 1.47). The use of total coping was between 2.35 and 2.48 in the intervention group (p = 0.015). Hope variables were better in the intervention group: optimism (p = 0.001), short- and long-term plans (p = 0.004), remembering happy moments (p = 0.039) and valuing life (p = 0.050). Conclusion: The use of prayer promotes an increase in religious/spiritual coping and hope. Brazilian Registry of Clinical Trials: RBR-4pphkf.